Preferential tariff formation: The case of the European Union - Vivek Joshi (Graduate Institute of International and Development Studies, 2010)
In this paper, we address the impact of multilateral trade liberalisation (MTL) on the preferential tariffs granted by the EU, which is one of the largest traders and one of the biggest contributors to MTL. We empirically address two important questions. First, if the MFN tariff for a product is higher, does it lead to a higher or lower preferential tariff? Second, the EU being a large trading partner in such agreements, does reciprocity matter for giving meaningful preferential access? For a given MFN tariff, we model the preferential tariff with a simple linear functional form. We draw three important conclusions. First, the products that are highly protected do not get high preferential access even at the regional level. Second, reciprocity plays only a limited role in granting better preferential access. Third, GSP preferences matters when the EU negotiates with the developed partners but it does not matter when it negotiates with the developing partners.
Keywords: F13; F15; 330; MFN tariffs; preferential tariffs; reciprocity; GSP; Meistbegünstigung; Handelsliberalisierung; Zollpräferenzen; EU-Staaten